2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5625971
|View full text |Cite
|
Sign up to set email alerts
|

PhysioDoloris: a monitoring device for Analgesia / Nociception balance evaluation using Heart Rate Variability analysis

Abstract: Continuous Analgesia / Nociception balance evaluation during general anesthesia could be of precious help for the optimization of analgesic drugs delivery, limiting the risk of toxicity due to the use of opioid drugs, limiting the risk of post operative hyper algesia, and, probably, reducing time of recovery after surgical procedure. Heart Rate Variability analysis has been shown in several studies to measure the Autonomic Nervous System tone, which is strongly influenced by anesthetic drugs. Recording RR seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 10 publications
1
105
0
7
Order By: Relevance
“…Several studies [36][37][38] relate nociception with the parameters derived from the analysis of heart rate variability (HRV). It has been demonstrated that the tone of the autonomic nervous system is strongly influenced by anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [36][37][38] relate nociception with the parameters derived from the analysis of heart rate variability (HRV). It has been demonstrated that the tone of the autonomic nervous system is strongly influenced by anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Son birkaç yılda, anestezinin dört temel öğesinden biri olan analjezi ve otonom reflekslerin, anestezistin deneyimi dışında objektif olarak değerlendirebilecek farklı parametreler üzerinde çalışılmıştır (24)(25). Bunlardan en önemlilerinden biri de çalışma grubumuzda kullandığımız ANİ'dir (8,9,26). KAH değişkenliğinden yararlanan bu indekste yeterli analjezi varlığında değişkenlik sadece solunumsal aritmiden kaynaklanır ve bu durum parasempatik tonus hakimiyetini gösterir.…”
Section: Discussionunclassified
“…Anestezi sırasında parasempatik otonom sinir sisteminin tonusunu ölçerek nosisepsiyon-analjezi dengesini ve dolayısıyla peroperatuvar dönemde analjezi yeterliliğini gösteren Analjezi Nosisepsiyon indeksi [ANİ, (Metrodolaris, Fransa)] yeni bir parametre olarak son yıllarda ortaya çıkmıştır (8,9). ANİ, kalp hızı varyasyonları içinde iki R dalgası arasındaki zaman aralığının solunum siklusu ile değişkenliğinin filtre edilerek ölçülmesi ve değerlendirilmesiyle elde edilen parasempatik tonusu (p∑) gösteren, 0-100 arasında değişen sayısal bir değerdir.…”
Section: Introductionunclassified
“…The Analgesia Nociception Index (ANI) monitor (MDMS, Loos, France) enables a real time analysis of the pS activity based on the ECG signal [31], by detecting each R peak and establishing the RR interval series over time (Figure 2).…”
Section: Monitoring Analgesiamentioning
confidence: 99%